Impact of periodic safety update reporting system: A preliminary trial in a tertiary care teaching hospital of southern India - Alkesh K. Lokhande, Mukhyaprana M. Prabhu, Surulivel Rajan Mallayasamy&, Girish Thunga P., Mazhuvancherry K. Unnikrishnan& (Journal of Applied Pharmaceutical Science, 2018)
The objective of this study was to assess the impact of implemented periodic safety update report (PSUR) system in our hospital via PSUR function assessment questionnaire (PFAQ) vetted by Delphi panel and by comparing frequency and rate of adverse drug reaction (ADR) reporting for three highly prescribed drugs. An PFAQ was validated by Delphi panel, in two successive rounds of revision and used to record the responses on Likert scale. Drugs with well-known ADR profiles in published literature were considered reliable markers of the impact of PSUR system implementation. Pre-PSUR retrospective data retrieved from medical records for 9 months and compared with the trend of frequency and rate of ADR reporting post-PSUR system implementation. Frequency and rate of ADR reporting for selected drugs rose by 68% post-PSUR system implementation. Participation of wards in ADR reporting and reporting of unexpected/unreported ADRs was also seen increased. Numbers of PFAQ responses for each performance indicator corresponding to the respective success factors were seen shifting favorably on the Likert scale in phase 2 study period. This study illustrates how drug safety reporting network can be established by reallocating existing resources, with minimal expenses on training/human resources and to improve poorly designed pharmacovigilance system in India that relies heavily on data from overseas.
Keywords: Periodic safety update report, pharmacovigilance, adverse drug reaction, Central Drug Standard Control Organization, drug Controller General of India.